Pengaruh Gaya Kepemimpinan Gembala Terhadap Pertumbuhan Spiritual Quotient Generasi Z - Andri; Panca Parulian; Liviana Pribadi; Dhwi Waspodo (STT INTI Bandung, 2024)
Leadership is integral to the structure and functioning of a church organization. A spiritual leader—such as a pastor—plays a crucial and strategic role in pastoral care, significantly impacting the spiritual growth of the congregation they serve. A congregation comprises individuals from diverse generational groups, each with varying levels of spiritual intelligence (Spiritual Quotient), which a leader must consider when determining their approach to pastoral leadership. One key factor contributing to an individual's spiritual intelligence is personal spiritual experience. This suggests that spiritual growth often originates internally (from the